Cloning, expression, purification, crystallization and preliminary X‐ray diffraction of a lysine‐specific permease from Pseudomonas aeruginosa. Issue 10 (1st October 2014) - Nji, Emmanuel; Li, Dianfan; Doyle, Declan A.; Caffrey, Martin
<x xml:space="preserve">Abstract</x> The prokaryotic lysine‐specific permease (LysP) belongs to the amino acid–polyamine–organocation (APC) transporter superfamily. In the cell, members of this family are responsible for the uptake and recycling of nutrients, for the maintenance of a constant internal ion concentration and for cell volume regulation. The detailed mechanism of substrate selectivity and transport of L‐lysine by LysP is not understood. A high‐resolution crystal structure would enormously facilitate such an understanding. To this end, LysP from Pseudomonas aeruginosa was recombinantly expressed in Escherichia coli and purified to near homogeneity by immobilized metal ion‐affinity chromatography (IMAC) and size‐exclusion chromatography (SEC). Hexagonal‐ and rod‐shaped crystals were obtained in the presence of L‐lysine and the L‐lysine analogue L‐4‐thialysine by vapour diffusion and diffracted to 7.5 Å resolution. The diffraction data were indexed in space group P21, with unit‐cell parameters a = 169.53, b = 169.53, c = 290.13 Å, γ = 120°.